Optimization of Ultrasound-Assisted Cold Brew Process to Develop Phenolics, Flavonoids, and Caffeine-Rich Coffee Beverage - Andika Wicaksono Putro; Fahmi Maulana Zulkarnaen; Aryudiana Sari; Sri Anggrahini; Widiastuti Setyaningsih (Indonesian Food and Nutrition Progress, 2021)
Ultrasound-assisted cold brew (UACB) method emerged as a solution of a long brew traditional cold brew method in coffee. Apart from the particular taste and odor, cold brew coffee contains a number of phenolic (TPC), flavonoid compounds (TFC), and caffeine. The level of these compounds in the drinks is strongly influenced by various factors related to extraction process, such as extraction temperature (x1: 4 and 25 °C), time (x2: 5,15, and 25 min), UAE duty cycle (x3: 20, 50, and 80 s-1), and grind size (x4: coarse and medium). Based on the TPC, TFC, and caffeine contents, the optimum condition was at 25 °C for 25 min with 80 s-1 UAE duty cycle and medium coffee grind size: with 2.40 ± 0.11 mg GAE/mL, 1.69 ± 0.05 mg RE/mL, and 1.10 ± 0.02 mg caffeine/mL, respectively. Compared with the traditional cold brew method, only the TPC and caffeine content were significantly lower than the UACB method (p < 0.05). Furthermore, the TPC and TFC were stable in 7-day refrigerator storage (p > 0.05). The IC50 values of UACB coffee were 7,487 mg/L for DPPH assay and 64,113 mg/L for ABTS assay.